Hyaluronic acid as neuropathic ulcer treatment: a case report - Viana García, Antonio; Palomo López, Patricia (Revista Internacional de Ciencias Podológicas, 2016)
The prevalence of diabetic polyneuropathy in Spain is 22% increasing with age, standing at less than 5% in patients between 15 and 19 years and reaching 29.8% in those aged 70 to 74 years age. Infection is an important complication in Diabetic Foot, frequently associated with minor amputation and even lower extremity amputation. The study presents a clinical case of a 68-year-old man who consulted for a diabetic foot ulcer in the metatarseal area of the right foot, diagnosed two years ago and without healing success. An exploration protocol of the diabetic food was made. Afterwards, a surgical debridement was done and a cure procedure with pure hyaluronic acid, a bandage and foot unloading was followed. After 69 days of treatment, a complete ulcer healing was achieved. After the injure healing, a biomechanical exploration was made and a plantar support was produced to avoid the reappearance of the injury because of local hyperpressure.